Prevalence and factors associated with anxiety, depression and stress in a COVID-19 nursing team - Ana Paula Appel; Ariana Rodrigues da Silva Carvalho; Reginaldo Passoni dos Santos (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To investigate the levels of anxiety, depression and stress and their associated factors, among nursing professionals who make up the team working against COVID-19 of a University Hospital in the south of Brazil. Method Exploratory, descriptive, cross-sectional study conducted from May to July 2020. Results From the total number of professionals, 53.8% had anxiety; 38.4% depression; and 40.3%, stress. Age, length of service in the profession, job satisfaction and work shift showed a statistically significant association with depression, while the employment contract, length of service in the UH, length of service in the unit prior to the opening of the COVID-19 unit and satisfaction at work showed a significant association with stress. Conclusions The nursing professionals of the COVID-19 team have important levels of anxiety, depression and stress, and the factors associated with depression and stress have been identified.